Pengaruh Model Pembelajaran Reciprocal Teaching Terhadap Hasil Belajar Siswa Kelas XI pada Materi di Bawah Tirani Jepang - Septiana; Djunaidi; Muhammad Fakhruddin (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
Abstract: Student learning outcomes are influenced by several factors, one of which is the learning model. Poor student learning outcomes depend on the learning model used. One learning model that can be used is the reciprocal teaching model. This learning model is implemented by forming small groups based on the principle of asking questions through teaching and giving examples. This study aims to determine the effect of reciprocal teaching learning models on the learning outcomes of 11th-grade students at IPS in SMA Negeri 57, Jakarta. This research method is quantitative, with a quasi-experimental, pretest-posttest, and control group design. The sample in this study consisted of 60 11th-grade IPS students: 30 students in the experimental class and 30 students in the control class. The pre-test results of the experimental class obtained an average value of 59.29 while the control class was 60.36. The post-test of the experimental class obtained an average value of 81.92 while the control class was 79.06. The data analysis technique used was the Kolmogorov-Smirnov Test with a significance result of 0.130 in the experimental class and 0.155 in the control class which showed that the data was normally distributed. Then the F-Test with a result of 0.872 to test homogeneous variance data, and the T-Test with a result of 0.000 at a significance level of α = 0.05 to test the hypothesis. The results showed that there was an influence of the reciprocal teaching-learning model on the learning outcomes of students in class XI IPS of SMA Negeri 57 Jakarta in the material Under Japanese Tyranny. Keywords: reciprocal teaching, learning outcomes, Under Japanese Tyranny. Abstrak: Hasil belajar siswa dipengaruhi oleh beberapa faktor salah satunya adalah model pembelajaran. Rendahnya hasil belajar siswa tergantung pada model pembelajaran yang digunakan. Salah satu model pembelajaran yang dapat digunakan adalah model reciprocal etaching. Cara penerapan model pembelajaran ini adalah dengan membentuk kelompok kecil yang didasarkan pada prinsip perumusan pertanyaan melalui pengajaran dan pemberian contoh. Penelitian ini bertujuan untuk mengetahui pengaruh modal pembelajaran reciprocal teaching terhadap hasil belajar siswa kelas XI IPS di SMA Negeri 57 Jakarta. Metode penelitian ini adalah kuantitatif dengan kuasi eksperimen dan desain penelitian pretest-posttest control group design. Sampel dalam penelitian ini berjumlah 60 siswa kelas XI IPS dengan kelas eksperimen berjumlah 30 siswa dan kelas kontrol berjumlah 30 siswa. Hasil pretest kelas eksperimen mendapatkan nilai rata-rata 59,29 sedangkan kelas kontrol 60,36. Posttest kelas eksperimen mendapatkan rata-rata nilai 81,92 sedangkan kelas kontrol 79,06. Teknik analisis data yang digunakan adalah Uji Kolmogorov-Smirnov dengan hasil signifikansi 0,130 pada kelas eksperimen dan 0,155 pada kelas kontrol yang menunjukkan data berdistribusi normal. Kemudian Uji-F dengan hasil 0,872 untuk menguji data varians homogen, serta Uji-T dengan hasil 0,000 pada taraf signifikansi α = 0,05 untuk menguji hipotesis. Hasil penelitian menunjukkan terdapat pengaruh pada model pembelajaran reciprocal teaching terhadap hasil belajar siswa kelas XI IPS SMA Negeri 57 Jakarta pada materi di Bawah Tirani Jepang. Kata Kunci: reciprocal teaching, hasil belajar, di Bawah Tirani Jepang.